(untitled) - Franova, Lubica; Klapita, Vladimir (Doprava a spoje, 2006)
Logistic centers are important part of logistic chain infrastructure. When designing and creating logistic centers infrastructure in the given locality, it is necessary to follow specific system process to the logistic centers could execute required functions within the frame of logistic chain to their functional network could be created. In the paper are indicated system process for designing and creating logistic centers in the case of predefined locality.